2023
DOI: 10.1002/advs.202205744
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Conductive Multiscale Nerve Guidance Conduit with Hierarchical Fibers for Peripheral Nerve Regeneration

Abstract: Nerve guidance conduits (NGCs) have become a promising alternative for peripheral nerve regeneration; however, the outcome of nerve regeneration and functional recovery is greatly affected by the physical, chemical, and electrical properties of NGCs. In this study, a conductive multiscale filled NGC (MF-NGC) consisting of electrospun poly(lactide-co-caprolactone) (PCL)/collagen nanofibers as the sheath, reduced graphene oxide /PCL microfibers as the backbone, and PCL microfibers as the internal structure for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…The commonly recognized designs within nerve guides include hollow architectures, groove formations, multichannel arrangements, and internally filled structures utilizing fibers, sponges, hydrogels, etc. The hydrogel, which emulates the extracellular matrix, exhibits high water content, creates a three-dimensional (3D) microenvironment for cellular activities, and allows for the incorporation of chemical molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The commonly recognized designs within nerve guides include hollow architectures, groove formations, multichannel arrangements, and internally filled structures utilizing fibers, sponges, hydrogels, etc. The hydrogel, which emulates the extracellular matrix, exhibits high water content, creates a three-dimensional (3D) microenvironment for cellular activities, and allows for the incorporation of chemical molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…114 It was reported that a conductive multiscale NGC (MF-NGC) had a positive effect on neurite outgrowth of neuronal cells, and hierarchically arranged fibers promoted the regeneration of peripheral nerve tissues (Figure 7A). 115 In contrast, electrical stimulation has demonstrated to enhance cell proliferation and growth. Jiang et al fabricated a conductive composite conduit with alignment structure for nerve regeneration.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…(iii) H&E staining. Source: Reproduced under terms of the CC-BY license 115. Copyright 2023, The Authors, published by John Wiley and Sons.…”
mentioning
confidence: 99%
“…Despite the occurrence of direct-current electric fields in developing and regenerating nerve tissue, the potential significance of these electric fields has been largely overlooked in many of the hydrogel-based nerve regeneration reports. , Nevertheless, some studies have highlighted the significance of the bioink’s electroactivity as the key factor in developing NGC-specific bioinks for bioprinting purposes. , An electrically conductive hydrogel was developed by incorporating reduced graphene oxide (rGO) into GelMA for the production of NGCs . The composite bioink (GelMA/rGO) demonstrated enhanced neuritogenesis of PC12 cells in vitro and significantly enhanced sciatic nerve regeneration in rat models, compared to the pure GelMA due to the improved conductivity.…”
Section: Introductionmentioning
confidence: 99%